Copy-number variation of the NPHP1 gene in patients with juvenile Nephronophthisis. Issue 1 (2nd January 2021) - Abdelwahed, Mayssa; Maaloul, Ines; Benoit, Valerie; Hilbert, Pascale; Hachicha, Mongia; Kamoun, Hassen; Keskes-Ammar, Leila; Belguith, Neila
ABSTRACT: Objective : Juvenile nephronophthisis (NPHP) is an autosomal recessive cystic disease of the kidney. It represents the most frequent genetic cause of chronic renal failure in children. Methods : we investigated clinical and molecular features in two children with Juvenile nephronophthisis using firstly Multiplex ligation-dependent probe amplification (MLPA) and secondly multiplex PCR. Results : we report a homozygous NPHP1 deletion in two children. Conclusion : NPHP1 deletion analysis using diagnostic methods (e.g. MLPA, Multiplex PCR) should always be considered in patients with nephronophthisis, especially from consanguineous families. Our results provide insights into genotype-phenotype correlations in juvenile nephronophthisis that can be utilized in genetic counseling.